Surgical management of an enterocutaneous umbilical fistula caused by an incarcerated Richter's hernia in a one‐year‐old Quarter Horse filly. (19th February 2019) - Sommerfeld, T. C.; Röcken, M.; Al Naem, M.; Geburek, F.
Summary: This article reports a case of a one‐year‐old Quarter Horse filly with an enterocutaneous fistula resulting from an umbilical hernia since birth, treated successfully by en bloc resection of the hernial sac with the fistula and closure of the ileum with a modified Heineke‐Mikulicz technique. This consisted of closing the intestinal wound transversely to the long axis after excision of the fistula to help preserve a sufficient intestinal lumen and prevent potential stricture formation after longitudinal closure. Umbilical hernias are reported to have an incidence of 0.5–2.0% usually resolve spontaneously. Reducible hernias do not represent a surgical emergency whereas incarcerations should always undergo surgery as soon as possible. Enterocutaneous fistulae occur uncommonly as a result of congenital umbilical herniae that developed spontaneously into Richter's herniae or Littré herniae or they are induced traumatically or iatrogenically after therapeutic attempts. In most cases, enterocutaneous fistulae do not require immediate surgery. However, the excision of the fistula should be scheduled within a few days after diagnosis. In the current case, the owner reported a healthy development of the filly after 1 year without any functional problems. This case represents an example of successful use of the Heineke‐Mikulicz technique to establish an alternative to standard end‐to‐end anastomosis.